The Development of Learning Tolerance Values Religious in the Ogoh-ogoh Tourism Education in Balun Village - Kartika Herlina Candraning Shiam; I Nyoman Lodra (Universitas PGRI Kanjuruhan Malang, 2020)
The purpose of writing this article is to produce an educational tour package that invites tourists and students to travel, interact and learn about tolerance through the art of making Ogoh-ogoh that teaches the values of religious tolerance in Balun Village. The approach used in this research is Research and Development by choosing 4-D stages, 1.) Define by observing, interviewing and documenting in the form of photos and videos, 2.) Design designing educational tour packages, 3.) Developing with realize and test tour packages, 4.) Dissemination revision and distribution. The results of this study are educational tour packages about tolerance values that are manifested from the mutual cooperation in the celebration of Ogoh-ogoh without distinguishing the religions they profess. This package also invites students to make a statue of Ogoh-ogoh together with a plural community in Balun. so that it can be used as one of the character education for tourists and students as souvenirs that can be practiced in social life by manifesting through the symbol of the Declaration of Tolerance Movement.